Elusive physiological role of prostatic acid phosphatase (PAP): generation of choline for sperm motility via auto-and paracrine cholinergic signaling - Hanley, Peter J. (Frontiers in Physiology, 2023)
Prostatic acid phosphatase (PAP) exists as two splice variants, secreted PAP and transmembrane PAP, the latter of which is implicated in antinociceptive signaling in dorsal root ganglia. However, PAP is predominantly expressed in the prostate gland and the physiological role of seminal PAP, first identified in 1938, is largely unknown. Here, the author proposes that PAP, following ejaculation, functions to hydrolyze phosphocholine (PC) in seminal fluid and generate choline, which is imported by sperm via a choline transporter and converted to acetylcholine (ACh) by choline acetyltransferase. Auto- and paracrine cholinergic signaling, or choline directly, may subsequently stimulate sperm motility via α7 nicotinic ACh receptors (nAChRs) and contractility of the female reproductive tract through muscarinic ACh receptors (mAChRs). Consistent with a role of PAP in cholinergic signaling, 1) seminal vesicles secrete PC, 2) the prostate gland secretes PAP, 3) PAP specifically catalyzes the hydrolysis of PC into inorganic phosphate and choline, 4) seminal choline levels increase post-ejaculation, 5) pharmacological inhibition of choline acetyltransferase inhibits sperm motility, 6) inhibition or genetic deletion of α7 nAChRs impairs sperm motility, and 7) mAChRs are expressed in the uterus and oviduct (fallopian tube). Notably, PAP does not degrade glycerophosphocholine (GPC), the predominant choline source in the semen of rats and other mammals. Instead, uterine GPC phosphodiesterases may liberate choline from seminal GPC. In summary, the author deduces that PAP in humans, and uterine GPC phosphodiesterases in other mammals, function to generate choline for sperm cholinergic signaling, which promotes sperm motility and possibly contractility of the female reproductive tract.